Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Social infrastructure and centralisation in community response and recovery from disasters - Petr Matous; Scott Webster; Emma Pittaway; Jodie Bailie; Jo Longman; Nader Naderpajouh; Michele Barnes; Danielle Celermajer; David Schlosberg (Natural Hazards, 2026)
Response and recovery from climate-related disasters typically involve a mixture of formal and informal organising. There is an old and ongoing general debate about the efficiency and impact of formal versus informal organising, but evidence about the specific structures of these forms of response and recovery is lacking. In this study, we interviewed 68 informants from three different Australian communities impacted by floods and fires and conducted social network modelling to explore how formal and informal organising evolve, interact, complement and potentially come into tension with each other in response and recovery from compounding disasters. We explicitly measured and analysed the topology of community networks that are formed, mobilised and reshaped before and after disasters. Our focus is on how local community networks evolve in terms of centralisation—the extent to which a few key actors dominate coordination efforts—and reciprocity—the degree to which support and resources flow mutually between network members. The results across the three contexts provide empirical evidence on how centralisation combined with reciprocity can be mobilised during response and recovery to serve the communities and their resilience. The findings regarding the vital processes of shifting centralisation in disaster response and recovery can inform debates on frictions between formal and informal patterns of organising and illuminate how communities can most effectively respond to natural hazards within their local context.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

System-wide assessment of plastic pollution in Indonesia: external stakeholder mapping - Spyridoula Gerassimidou; Mike Webster; Andre Kuncoroyekti; David C. Wilson; Susan Jobling; Eddy Soedjono; Elena Lovat; Eleni Iacovidou (Environment Systems and Decisions, 2025)
Recent global initiatives, such as the Global Plastics Treaty, highlight the urgency for a systems-based approach to address the risks associated with plastic pollution. However, the implementation of such initiatives is often hindered by the absence of clear criteria for what constitutes a systemic approach and who is included within it. This study offers a comprehensive analysis of external stakeholders, those who are not directly engaged in the physical flow of plastics, contrasted with internal stakeholders, who play direct roles in the physical production, consumption and waste generation and management. While internal stakeholders have traditionally received increased attention in value chain studies, external stakeholders remain largely overlooked. To address this gap, this research introduces a novel approach, embedded in the systems-based method, called Complex Value Optimisation for Resource Recovery (CVORR), to identify, map and categorise external stakeholders in the plastics value chain in Banyuwangi, Indonesia, based on organisation type, activities, and interest. The study reveals a complex system of 111 external stakeholders consolidated into 11 groups that are engaged across various operational stages and spatial levels. By integrating stakeholder theory and analytical tools such as the Mendelow matrix, the study uncovers underlying power dynamics and significant lock-ins that arise where the emphasis on downstream waste management overshadows preventive upstream measures. The findings highlight the importance of fostering communication and collaboration among stakeholders and creating partnerships within and across stakeholder groups to drive systemic change. Engaging effectively throughout the plastics value chain can pave the way for tailored solutions to local challenges, thereby enhancing sustainability and facilitating alignment with the Sustainable Development Goals. Ultimately, this study advocates for coordinated efforts, ensuring that policy interventions and local actions support a comprehensive, circular approach to effective plastics management.

Coupled micro-computed tomography and micromechanical experiment on the failure of discontinuous porphyry rock - Sarah Webster; Nicolas Francois; Edward Andò; Mark Knackstedt; David Beck; Mohammad Saadatfar (International Journal of Rock Mechanics and Mining Sciences, 2025)

Quantification of methyl glyoxal in New Zealand Mānuka honey and honey meads - Claire E. Webster; David Barker; Rebecca C. Deed; Lisa I. Pilkington (Food Chemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Mead production and quality: A review of chemical and sensory mead quality evaluation with a focus on analytical methods - Claire E. Webster; David Barker; Rebecca C. Deed; Lisa I. Pilkington (Food Research International, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Fundamentals of wildlife dosimetry and lessons learned from a decade of measuring external dose rates in the field - Thomas G. Hinton; Donovan Anderson; Edda Bæk; Vikas C. Baranwal; James C. Beasley; Helen L. Bontrager; David Broggio; Justin Brown; Michael E. Byrne; Hannah C. Gerke; Hiroko Ishiniwa; Stacey L. Lance; et al. (Journal of Environmental Radioactivity, 2024)

Comparative genomics identifies key adaptive traits of sponge‐associated microbial symbionts - Paul A. O'Brien; Steven J. Robbins; Shangjin Tan; Laura Rix; David J. Miller; Nicole S. Webster; Guojie Zhang; David G. Bourne (Environmental Microbiology, 2024)
Sponge microbiomes are often highly diverse making it difficult to determine which lineages are important for maintaining host health and homeostasis. Characterising genomic traits associated with symbiosis can improve our knowledge of which lineages have adapted to their host and what functions they might provide. Here we examined five microbial families associated with sponges that have previously shown evidence of cophylogeny, including Endozoicomonadaceae, Nitrosopumilaceae, Spirochaetaceae, Microtrichaceae and Thermoanaerobaculaceae , to better understand the mechanisms behind their symbiosis. We compared sponge‐associated genomes to genomes found in other environments and found that sponge‐specific clades were enriched in genes encoding many known mechanisms for symbiont survival, such as avoiding phagocytosis and defence against foreign genetic elements. We expand on previous knowledge to show that glycosyl hydrolases with sulfatases and sulfotransferases likely form multienzyme degradation pathways to break and remodel sulfated polysaccharides and reveal an enrichment in superoxide dismutase that may prevent damage from free oxygen radicals produced by the host. Finally, we identified novel traits in sponge‐associated symbionts, such as urea metabolism in Spirochaetaceae which was previously shown to be rare in the phylum Spirochaetota. These results identify putative mechanisms by which symbionts have adapted to living in association with sponges.

Joint prioritization of best-management-practice projects to optimally improve agricultural-drain-outlet water quality - Dylan R. Harp; Eleanor A. Bash; Anthony S. Orlando; Tommy Franzen; Dion Webster; Stephanie Tatge; Andrew Knight; Jesse Naymik; David Primozich (Journal of Hydrology, 2024)

Validation of key sponge symbiont pathways using genome‐centric metatranscriptomics - Paul A. O'Brien; Shangjin Tan; Pedro R. Frade; Steven J. Robbins; J. Pamela Engelberts; Sara C. Bell; Inka Vanwonterghem; David J. Miller; Nicole S. Webster; Guojie Zhang; David G. Bourne (Environmental Microbiology, 2023)
The sponge microbiome underpins host function through provision and recycling of essential nutrients in a nutrient poor environment. Genomic data suggest that carbohydrate degradation, carbon fixation, nitrogen metabolism, sulphur metabolism and supplementation of B‐vitamins are central microbial functions. However, validation beyond the genomic potential of sponge symbiont pathways is rarely explored. To evaluate metagenomic predictions, we sequenced the metagenomes and metatranscriptomes of three common coral reef sponges: Ircinia ramosa , Ircinia microconulosa and Phyllospongia foliascens . Multiple carbohydrate active enzymes were expressed by Poribacteria, Bacteroidota and Cyanobacteria symbionts, suggesting these lineages have a central role in assimilating dissolved organic matter. Expression of entire pathways for carbon fixation and multiple sulphur compound transformations were observed in all sponges. Gene expression for anaerobic nitrogen metabolism (denitrification and nitrate reduction) were more common than aerobic metabolism (nitrification), where only the I. ramosa microbiome expressed the nitrification pathway. Finally, while expression of the biosynthetic pathways for B‐vitamins was common, the expression of additional transporter genes was far more limited. Overall, we highlight consistencies and disparities between metagenomic and metatranscriptomic results when inferring microbial activity, while uncovering new microbial taxa that contribute to the health of their sponge host via nutrient exchange.

Life‐stage specificity and cross‐generational climate effects on the microbiome of a tropical sea urchin (Echinodermata: Echinoidea) - Emma Marangon; Sven Uthicke; Frances Patel; Ezequiel M. Marzinelli; David G. Bourne; Nicole S. Webster; Patrick W. Laffy (Molecular Ecology, 2023)
Microbes play a critical role in the development and health of marine invertebrates, though microbial dynamics across life stages and host generations remain poorly understood in most reef species, especially in the context of climate change. Here, we use a 4‐year multigenerational experiment to explore microbe–host interactions under the Intergovernmental Panel on Climate Change (IPCC)‐forecast climate scenarios in the rock‐boring tropical urchin Echinometra sp. A . Adult urchins (F 0 ) were exposed for 18 months to increased temperature and p CO 2 levels predicted for years 2050 and 2100 under RCP 8.5, a period which encompassed spawning. After rearing F 1 offspring for a further 2 years, spawning was induced, and F 2 larvae were raised under current day and 2100 conditions. Cross‐generational climate effects were also explored in the microbiome of F 1 offspring through a transplant experiment. Using 16S rRNA gene sequence analysis, we determined that each life stage and generation was associated with a distinct microbiome, with higher microbial diversity observed in juveniles compared to larval stages. Although life‐stage specificity was conserved under climate conditions projected for 2050 and 2100, we observed changes in the urchin microbial community structure within life stages. Furthermore, we detected a climate‐mediated parental effect when juveniles were transplanted among climate treatments, with the parental climate treatment influencing the offspring microbiome. Our findings reveal a potential for cross‐generational impacts of climate change on the microbiome of a tropical invertebrate species.

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

Use of electrical resistivity tomography to reveal the shallow freshwater–saline interface in The Fens coastal groundwater, eastern England (UK) - Mitchell Moulds; Iain Gould; Isobel Wright; David Webster; Daniel Magnone (Hydrogeology Journal, 2023)
The Fens is a region that contributes 11% of the agri-food economy from just 4% of the agricultural land covering England (UK). This region is vulnerable to soil salinisation from sea-level rise with estimated 100-year flood events projected to be observed up to every 2 years by 2100. Seawater intrusion and upwelling of saline groundwater can provide an additional pathway; however, the area’s groundwater has not been assessed and the risk is unknown. This study used data from the British Geological Survey’s stratigraphic core archive to produce the first stratigraphic map of the loosely consolidated Holocene deposits in the South Holland–Holbeach Marsh region. There is a sandy unconfined aquifer towards the coast, a semiconfined central region with a silty cap and a clay confining cap in the north region. Electrical resistivity tomography data indicate water level depths of 0.58 ± 0.37 m above mean sea level (msl) in February 2021 and 0.01 ± 0.72 m msl in August 2021. The saline–freshwater boundary was at 1.70 ± 0.82 m msl in February 2021, deepening to 2.00 ± 1.02 m msl in August 2021, but the only evidence of seasonal fluctuation was within 10 km of the coast. A potential, but unverified, freshwater lens up to 3.25 m thick may exist beneath the surface. These results suggest that freshwater–saline interface fluctuations may primarily be driven by surface hydrology and would be vulnerable to climate-change-induced future variations in factors that affect surface water.

Unravelling the synergism of catalytic oxidation and filtration in Co-Mn-oxide impregnated ceramic membrane for intensified degradation of recalcitrant micropollutant with peroxymonosulfate - Arvin Liangdy; Wen Jie Lee; Panyawut Tonanon; Richard David Webster; Shane Allen Snyder; Teik-Thye Lim (Chemical Engineering Journal, 2023)

The addition of carbon nanotubes modifies the biological, physicochemical, and electrical properties of carbon nanofiber composites - Sebastian Wilk; David Medina-Cruz; Marcel Zambrzycki; Piotr K. Szewczyk; Marek Nocuń; Elżbieta Menaszek; Thomas J. Webster; Aleksandra Benko (Chemical Engineering Journal, 2023)

Transcriptome Changes in Retinal Pigment Epithelium Post-PNU-282987 Treatment Associated with Adult Retinal Neurogenesis in Mice - Sarah E. Webster; Jake B. Spitsbergen; David M. Linn; Mark K. Webster; Deborah Otteson; Cynthia Cooley-Themm; Cindy L. Linn (Journal of Molecular Neuroscience, 2022)

Copepod interaction with small‐scale, dissipative eddies in turbulence: Comparison among three marine species - Dorsa Elmi; Donald R. Webster; David M. Fields (Limnology and Oceanography, 2022)
A physical model of a Burgers vortex was created in the laboratory with characteristics corresponding to dissipative‐scale eddies that copepods are likely to encounter in turbulent flows. The swimming behavior of three marine copepod species is assessed as a function of vortex strength in and around the flow structure with the vortex axis aligned vertically or horizontally in the water. The studied species are Acartia tonsa , an estuarine copepod with a hop‐sink swimming style; Temora longicornis , a coastal copepod with a cruise swimming style; and Calanus finmarchicus , an open‐ocean copepod with a cruise‐sink swimming style. The results show that copepods change their swimming behavior with the intensity of the Burgers vortex and reveal species‐specific responses in nearly all kinematic parameters. A. tonsa and C. finmarchicus exhibited the strongest behavioral response to increasing vortex strength and T. longicornis exhibited the weakest response. A. tonsa and T. longicornis showed no response to changes in vortex orientation, whereas the behavior of C. finmarchicus revealed some vortex orientation dependence. One common behavior among the species is that the swimming trajectory shape becomes increasingly curved and spiral around the vortex core with increasing vortex strength, which provides a means of local aggregation and increased encounter rate with food and mates. The results are interpreted in relation to differences in swimming style and setal morphology among the species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Protease-activated receptor 2 activation induces behavioural changes associated with depression-like behaviour through microglial-independent modulation of inflammatory cytokines - Serge Moudio; Ashleigh Willis; Karolina Pytka; Roua Abulkassim; Ros R. Brett; Jack F. Webster; Christian Wozny; Mark Barbour; Hui-Rong Jiang; David G. Watson; Josie C. van Kralingen; Scott M. MacKenzie; et al. (Psychopharmacology, 2022)
Rationale Major depressive disorder (MDD) is a leading cause of disability worldwide but currently prescribed treatments do not adequately ameliorate the disorder in a significant portion of patients. Hence, a better appreciation of its aetiology may lead to the development of novel therapies. Objectives In the present study, we have built on our previous findings indicating a role for protease-activated receptor-2 (PAR2) in sickness behaviour to determine whether the PAR2 activator, AC264613, induces behavioural changes similar to those observed in depression-like behaviour. Methods AC264613-induced behavioural changes were examined using the open field test (OFT), sucrose preference test (SPT), elevated plus maze (EPM), and novel object recognition test (NOR). Whole-cell patch clamping was used to investigate the effects of PAR2 activation in the lateral habenula with peripheral and central cytokine levels determined using ELISA and quantitative PCR. Results Using a blood–brain barrier (BBB) permeable PAR2 activator, we reveal that AC-264613 (AC) injection leads to reduced locomotor activity and sucrose preference in mice but is without effect in anxiety and memory-related tasks. In addition, we show that AC injection leads to elevated blood sera IL-6 levels and altered cytokine mRNA expression within the brain. However, neither microglia nor peripheral lymphocytes are the source of these altered cytokine profiles. Conclusions These data reveal that PAR2 activation results in behavioural changes often associated with depression-like behaviour and an inflammatory profile that resembles that seen in patients with MDD and therefore PAR2 may be a target for novel antidepressant therapies.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Differential and interacting impacts of invasive plants and white-tailed deer in eastern U.S. forests - David L. Gorchov; Bernd Blossey; Kristine M. Averill; Andrea Dávalos; J. Mason Heberling; Michael A. Jenkins; Susan Kalisz; William J. McShea; Janet A. Morrison; Victoria Nuzzo; Christopher R. Webster; Donald M. Waller (Biological Invasions, 2021)

Water safety attitudes, risk perception, experiences, and education for households impacted by the 2018 Camp Fire, California - Tolulope O. Odimayomi; Caitlin R. Proctor; Qi Erica Wang; Arman Sabbaghi; Kimberly S. Peterson; David J. Yu; Juneseok Lee; Amisha D. Shah; Christian J. Ley; Yoorae Noh; Charlotte D. Smith; Jackson P. Webster; et al. (Natural Hazards, 2021)

Testing cophylogeny between coral reef invertebrates and their bacterial and archaeal symbionts - Paul A. O’Brien; Nikos Andreakis; Shangjin Tan; David J. Miller; Nicole S. Webster; Guojie Zhang; David G. Bourne (Molecular Ecology, 2021)
Marine invertebrates harbour a complex suite of bacterial and archaeal symbionts, a subset of which are probably linked to host health and homeostasis. Within a complex microbiome it can be difficult to tease apart beneficial or parasitic symbionts from nonessential commensal or transient microorganisms; however, one approach is to detect strong cophylogenetic patterns between microbial lineages and their respective hosts. We employed the Procrustean approach to cophylogeny (PACo) on 16S rRNA gene derived microbial community profiles paired with COI, 18S rRNA and ITS1 host phylogenies. Second, we undertook a network analysis to identify groups of microbes that were co‐occurring within our host species. Across 12 coral, 10 octocoral and five sponge species, each host group and their core microbiota (50% prevalence within host species replicates) had a significant fit to the cophylogenetic model. Independent assessment of each microbial genus and family found that bacteria and archaea affiliated to Endozoicomonadaceae , Spirochaetaceae and Nitrosopumilaceae have the strongest cophylogenetic signals. Further, local Moran's I measure of spatial autocorrelation identified 14 ASVs, including Endozoicomonadaceae and Spirochaetaceae , whose distributions were significantly clustered by host phylogeny. Four co‐occurring subnetworks were identified, each of which was dominant in a different host group. Endozoicomonadaceae and Spirochaetaceae ASVs were abundant among the subnetworks, particularly one subnetwork that was exclusively comprised of these two bacterial families and dominated the octocoral microbiota. Our results disentangle key microbial interactions that occur within complex microbiomes and reveal long‐standing, essential microbial symbioses in coral reef invertebrates.

Microbiome-mediated mechanisms contributing to the environmental tolerance of reef invertebrate species - Emma Marangon; Patrick W. Laffy; David G. Bourne; Nicole S. Webster (Marine Biology, 2021)

Spotlight on how microbes influence their host's behavior - Laure Weisskopf; Irene L. G. Newton; David Berry; Nicole S. Webster (Environmental Microbiology, 2019)

New diagnostic descriptions and distribution information for Shepherd's beaked whale ( Tasmacetus shepherdi ) off Southern Australia and New Zealand - David M. Donnelly; Paul Ensor; Peter Gill; Rohan H. Clarke; Karen Evans; Michael C. Double; Trudi Webster; Will Rayment; Natalie T. Schmitt (Marine Mammal Science, 2018)

Elucidating the sponge stress response; lipids and fatty acids can facilitate survival under future climate scenarios - Holly Bennett; James J. Bell; Simon K. Davy; Nicole S. Webster; David S. Francis (Global Change Biology, 2018)
Ocean warming ( OW ) and ocean acidification ( OA ) are threatening coral reef ecosystems, with a bleak future forecast for reef‐building corals, which are already experiencing global declines in abundance. In contrast, many coral reef sponge species are able to tolerate climate change conditions projected for 2100. To increase our understanding of the mechanisms underpinning this tolerance, we explored the lipid and fatty acid ( FA ) composition of four sponge species with differing sensitivities to climate change, experimentally exposed to OW and OA levels predicted for 2100, under two CO 2 Representative Concentration Pathways. Sponges with greater concentrations of storage lipid, phospholipids, sterols and elevated concentrations of n ‐3 and n ‐6 long‐chain polyunsaturated FA ( LC PUFA ), were more resistant to OW . Such biochemical constituents likely contribute to the ability of these sponges to maintain membrane function and cell homeostasis in the face of environmental change. Our results suggest that n ‐3 and n ‐6 LC PUFA are important components of the sponge stress response potentially via chain elongation and the eicosanoid stress‐signalling pathways. The capacity for sponges to compositionally alter their membrane lipids in response to stress was also explored using a number of specific homeoviscous adaptation ( HVA ) indicators. This revealed a potential mechanism via which additional CO 2 could facilitate the resistance of phototrophic sponges to thermal stress through an increased synthesis of membrane‐stabilizing sterols. Finally, OW induced an increase in FA unsaturation in phototrophic sponges but a decrease in heterotrophic species, providing support for a difference in the thermal response pathway between the sponge host and the associated photosymbionts. Here we have shown that sponge lipids and FA are likely to be an important component of the sponge stress response and may play a role in facilitating sponge survival under future climate conditions.

Ice sheets and genetics: Insights into the phylogeography of Scottish Atlantic salmon, Salmo salar L. - Eef Cauwelier; Eric Verspoor; Mark W. Coulson; Anja Armstrong; David Knox; Lee Stradmeyer; Lucy M.I. Webster; John Gilbey (Journal of Biogeography, 2018)
Aim We constructed an independent phylogeographical hypothesis ( IPH ) for Atlantic salmon ( Salmo salar L.) in Scotland and adjacent northern England and tested if the distribution of contemporary microsatellite variation accorded with the IPH . Location NW Europe. Methods Knowledge of post‐Last Glacial Maximum ( LGM ) landscape development and salmon biology were used to define a temporal sequence of late Quaternary ecological niche models and, combined with the central‐marginal ( CM ) model of diversity evolution, to formulate an IPH . Observed microsatellite locus variation for salmon from 102 rivers in Scotland and northern England was tested for agreement with the IPH . Results The IPH postulated (1) initial colonization ( c. 17 ka bp ) of multiple isolated deglaciating coastal regions by long‐distance dispersal, predominantly from SW Europe via the Atlantic, (2) intra‐region colonization dominated by local range expansion, (3) differentiation by founder effects/genetic drift, in line with CM , until deglaciation complete and regions merged ( c . 10 ka bp ). IPH regions were weakly but significantly differentiated, showed broad agreement with genetically defined regions, and genetic diversity within them positively correlated with time post‐deglaciation, conforming to the CM model. The greatest differentiation was seen for the most recently diverged populations, with evidence that accumulating homoplastic mutations muted older regional phylogeographical signatures. Main conclusions Microsatellite differentiation in Scottish Atlantic salmon is significantly but weakly conditioned by post‐ LGM deglaciation, with a mosaic of regional groups and a temporal cascade of within‐region CM effects caused by local range expansion as patches became deglaciated. Colonization was predominantly or exclusively from the south‐western European LGM refugium. Accumulating homoplastic mutations have increasingly reduced regional differentiation.

Bird community responses to afforested eucalyptus plantations in the Argentine pampas - Colin C. Phifer; Jessie L. Knowlton; Christopher R. Webster; David J. Flaspohler; Julian A. Licata (Biodiversity and Conservation, 2017)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Microbial indicators as a diagnostic tool for assessing water quality and climate stress in coral reef ecosystems - Bettina Glasl; Nicole S. Webster; David G. Bourne (Marine Biology, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Identifying avian sources of faecal contamination using sterol analysis - Megan L. Devane; David Wood; Andrew Chappell; Beth Robson; Jenny Webster-Brown; Brent J. Gilpin (Environmental Monitoring and Assessment, 2015)

AVPR1A Variation in Chimpanzees (Pan troglodytes): Population Differences and Association with Behavioral Style - Stephanie F. Anestis; Timothy H. Webster; Jason M. Kamilar; M. Babette Fontenot; David P. Watts; Brenda J. Bradley (International Journal of Primatology, 2014)

The involvement of gibberellin signalling in the effect of soil resistance to root penetration on leaf elongation and tiller number in wheat - Mauricio A. Coelho Filho; Ellen H. Colebrook; David P. A. Lloyd; Colin P. Webster; Sacha J. Mooney; Andrew L. Phillips; Peter Hedden; William R. Whalley (Plant and Soil, 2013)

Modelling the ancient maize agriculture potential of landforms in Tikal National Park, Guatemala - Chris S. Balzotti; David L. Webster; Tim M. Murtha; Steven L. Petersen; Richard L. Burnett; Richard E. Terry (International Journal of Remote Sensing, 2013)

An Aqueous Orally Active Vaccine Targeted Against a RAGE/AB Complex as a Novel Therapeutic for Alzheimer’s Disease - Scott J. Webster; Shyamala Mruthinti; William David Hill; Jerry J. Buccafusco; Alvin V. Terry (NeuroMolecular Medicine, 2012)

Analysis of climate policy targets under uncertainty - Mort Webster; Andrei P. Sokolov; John M. Reilly; Chris E. Forest; Sergey Paltsev; Adam Schlosser; Chien Wang; David Kicklighter; Marcus Sarofim; Jerry Melillo; Ronald G. Prinn; Henry D. Jacoby (Climatic Change, 2012)

Small Mammals Rule! - Wm. David Webster (Journal of Mammalian Evolution, 2011)

Plantations for Bioenergy: Principles for Maintaining Biodiversity in Intensively Managed Forests - David J. Flaspohler; Christopher R. Webster (Forest Science, 2011)
As the value of forests for providing a feedstock for bioenergy increases, more land will probably be converted to fast-growing tree plantations to increase short-term production of cellulose. In general, plantations support fewer plant and animal species than native forests because plantations are greatly simplified in terms of tree and other plant species richness and in terms of many structural and process-related forest functions. However, native biodiversity can be retained in some plantation forests if careful management is used in all stages of plantation establishment, tending, and harvest. Key considerations for conserving biodiversity as plantation forests grow as a proportion of total world forest cover include choice of plantation tree species, harvest frequency, rotation age, and care and management of biological legacies and forest understory plant and wildlife communities. We provide background and guidance that can be used to guide future plantation management in a new era of using forests to capture and store carbon and to generate bioenergy.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Caribbean octocorals record changing carbon and nitrogen sources from 1862 to 2005 - DAVID M. BAKER; KIRBY L. WEBSTER; KIHO KIM (Global Change Biology, 2010)
During the last century, the global biogeochemical cycles of carbon (C) and nitrogen (N) have been drastically altered by human activities. A century of land‐clearing and biomass burning, followed by fossil fuel combustion have increased the concentration of atmospheric CO 2 by approximately 20%, and since the mid‐1900s, the use of agricultural fertilizers has been the primary driver of an approximate 90% increase in bioavailable N. Geochemical records obtained through stable isotope analysis of terrestrial and marine biota effectively illustrate rising anthropogenic C inputs. However, there are fewer records of anthropogenic N, despite the enormous magnitude of change and the known negative effects of N on ecosystem health. We used stable isotope values from independent octocorals (gorgonians) sampled across the Western Atlantic over the last 143 years to document human perturbations of the marine C and N pools. Here, we demonstrate that in sea plumes δ 13 C values and in both sea plumes and sea fans δ 15 N values declined significantly from 1862 to 2005. Sea plume δ 13 C values were negatively correlated with increasing atmospheric CO 2 concentrations and corroborate known rates of change resulting from global fossil fuel combustion, known as the Suess effect. We suggest that widespread input of agricultural fertilizers to near‐shore coastal waters is the dominant driver for the decreasing δ 15 N trend, though multiple anthropogenic sources are likely affecting this trend. Given the interest in using δ 15 N as an indicator for N pollution in aquatic systems, we highlight the risk of underestimating contributions of pollutants as a result of source mixing as demonstrated by a simple isotope‐mixing model. We conclude that signals of major human‐induced perturbations of the C and N pools are detectable in specimens collected over wide geographic scales, and that archived materials are invaluable for establishing baselines against which we can assess environmental change.

Three amino acid changes in PB1-F2 of highly pathogenic H5N1 avian influenza virus affect pathogenicity in mallard ducks - Henju Marjuki; Christoph Scholtissek; John Franks; Nicholas J. Negovetich; Jerry R. Aldridge; Rachelle Salomon; David Finkelstein; Robert G. Webster (Archives of Virology, 2010)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

75 years of breeding pinto bean for resistance to diseases in the United States - Henry Terán; Margarita Lema; David Webster; Shree P. Singh (Euphytica, 2009)

Field assessment of an H5N1 inactivated vaccine in chickens and ducks in Lao PDR - David A. Boltz; Bounlom Douangngeun; Settha Sinthasak; Phouvong Phommachanh; Phetlamphone Midouangchanh; David Walker; Rachael Keating; Alexey M. Khalenkov; Mahesh Kumar; Robert G. Webster (Archives of Virology, 2009)

Enhancing the Engagement of U.S. Private Foundations with Conservation Science - ERIKA ZAVALETA; DANIEL C. MILLER; NICK SALAFSKY; ERICA FLEISHMAN; MICHAEL WEBSTER; BARRY GOLD; DAVID HULSE; MARY ROWEN; GARY TABOR; JACK VANDERRYN (Conservation Biology, 2008)
Funding for conservation is limited, and its investment for maximum conservation gain can likely be enhanced through the application of relevant science. Many donor institutions support and use science to pursue conservation goals, but their activities remain relatively unfamiliar to the conservation‐science community. We examined the priorities and practices of U.S.‐based private foundations that support biodiversity conservation. We surveyed 50 donor members of the Consultative Group on Biological Diversity (CGBD) to address three questions: (1) What support do CGBD members provide for conservation science? (2) How do CGBD members use conservation science in their grant making and strategic thinking? (3) How do CGBD members obtain information about conservation science? The 38 donor institutions that responded to the survey made $340 million in grants for conservation in 2005, including $62 million for conservation science. Individual foundations varied substantially in the proportion of conservation funds allocated to science. Foundations also varied in the ways and degree to which they used conservation science to guide their grant making. Respondents found it “somewhat difficult” to stay informed about conservation science relevant to their work, reporting that they accessed conservation science information mainly through their grantees. Many funders reported concerns about the strategic utility of funding conservation science to achieve conservation gains. To increase investment by private foundations in conservation science, funders, researchers, and conservation practitioners need to jointly identify when and how new scientific knowledge will lower barriers to conservation gains. We envision an evolving relationship between funders and conservation scientists that emphasizes primary research and synthesis motivated by (1) applicability, (2) human‐ecosystem interactions, (3) active engagement among scientists and decision makers, and (4) broader communication of relevant scientific information.

Support for the Giant Wave Hypothesis: evidence from submerged terraces off Lanai, Hawaii - Jody M. Webster; David A. Clague; Juan Carlos Braga (International Journal of Earth Sciences, 2007)

Robert Milton Silverstein 1916–2007 - Dietland Muller-Schwarze; James H. Tumlinson; Francis X. Webster; David L. Wood (Journal of Chemical Ecology, 2007)

The nucleus-encoded factor MCD4 participates in degradation of nonfunctional 3′ UTR sequences generated by cleavage of pre-mRNA in Chlamydomonas chloroplasts - Linda A. Rymarquis; Brian R. Webster; David B. Stern (Molecular Genetics and Genomics, 2007)

Environmental predictors of global parrot (Aves: Psittaciformes) species richness and phylogenetic diversity - Richard G. Davies; C. David L. Orme; Andrea J. Webster; Kate E. Jones; Tim M. Blackburn; Kevin J. Gaston (Global Ecology and Biogeography, 2007)
Aim Spatial patterns of phylogenetic diversity (PD) aid our ability to discern diversification rate mechanisms underlying hypotheses for the large‐scale distribution of biodiversity. We develop a predictive framework for the way in which spatial patterns of PD vary with those of species richness, depending on the balance between speciation and extinction rates. Within this framework, diversification processes thought to underlie the productive energy, ambient energy, topographic variability and habitat variety hypotheses predict that gradients of increase in species richness will be associated with: (1) decreasing extinction rates where driven by productive energy, hence increasing relative PD (i.e. PD controlling for species richness, or PD rel ); (2) a similar positive relationship between ambient energy and PD rel ; (3) increasing speciation rates where driven by topographic variability, hence decreasing PD rel ; and (4) no consistent relationship between PD rel and habitat variety when driven by the latter. We test these predictions using distributional data on parrots. Location Neotropical, Afrotropical, Indo‐Malayan and Australasian realms. Methods Spatial models were used to test the predictions. Results Globally, a positive association between productive energy and PD rel confirms prediction (1). However, within realms, hump‐shaped relationships suggest the importance of decreasing extinction rates up to a threshold level of productive energy, and the increasing importance of speciation rates thereafter. Ambient energy is positively associated with PD rel in Australasia, Indo‐Malaya, and globally, supporting prediction (2). However, this is driven by the coincidence of highest PD rel in areas of high ambient energy and intermediate productive energy (i.e. in seasonal tropical environments), which may be characterized by relatively low speciation and extinction rates. In the Neotropics, increasing topographic variability is associated with decreasing PD rel and increasing species richness, suggesting an increasing gradient of speciation, supporting prediction (3). Elsewhere, the signal of this mechanism may be obscured by collinearities with energy gradients. The lack of an overall relationship between habitat diversity and PD rel confirms prediction (4). Main conclusions Spatial patterns of PD rel in relation to environmental gradients may be sensitive to collinearities among those gradients. Nevertheless, patterns emerge which have implications for the relative importance of speciation and extinction processes in generating latitudinal diversity gradients.

Analysis of families with common variable immunodeficiency (CVID) and IgA deficiency suggests linkage of CVID to chromosome 16q - Alejandro A. Schäffer; Jessica Pfannstiel; A. David B. Webster; Alessandro Plebani; Lennart Hammarström; Bodo Grimbacher (Human Genetics, 2006)

Submicro Scale NMR Sample Preparation for Volatile Chemicals - Satoshi Nojima; David J. Kiemle; Francis X. Webster; Wendell L. Roelofs (Journal of Chemical Ecology, 2004)

Uncertainty Analysis of Climate Change and Policy Response - Mort Webster; Chris Forest; John Reilly; Mustafa Babiker; David Kicklighter; Monika Mayer; Ronald Prinn; Marcus Sarofim; Andrei Sokolov; Peter Stone; Chien Wang (Climatic Change, 2003)

Is crustacean hyperglycaemic hormone precursor-related peptide a circulating neurohormone in crabs? - David Wilcockson; Sook Chung; Simon Webster (Cell and Tissue Research, 2002)

In Vivo Three-Dimensional Surface Geometry of Abdominal Aortic Aneurysms - Michael S. Sacks; David A. Vorp; M. L. Raghavan; Michael P. Federle; Marshall W. Webster (Annals of Biomedical Engineering, 1999)

Gene Expression Is Altered in Perfused Arterial Segments Exposed to Cyclic Flexure Ex Vivo - David A. Vorp; David G. Peters; Marshall W. Webster (Annals of Biomedical Engineering, 1999)

Decreased gap-junctional communication associated with segregation of the neuronal phenotype in the RT4 cell-line family - L. M. Donahue; Daniel R. Webster; Ivvanee Martinez; David C. Spray (Cell and Tissue Research, 1998)

Genetic diversity of North American and Old World Saccharum assessed by RAPD analysis - David M. Burner; Yong-Bao Pan; Robert D. Webster (Genetic Resources and Crop Evolution, 1997)

Ex vivo biomechanical behavior of abdominal aortic aneurysm: Assessment using a new mathematical model - M. L. Raghavan; Marshall W. Webster; David A. Vorp (Annals of Biomedical Engineering, 1996)

Modeling the transmural stress distribution during healing of bioresorbable vascular prostheses - David A. Vorp; M. L. Raghavan; Harvey S. Borovetz; Howard P. Greisler; Marshall W. Webster (Annals of Biomedical Engineering, 1995)

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)